The opposing roles of CD4+ T cells in anti‐tumour immunity. Issue 4 (23rd May 2018) - Ahrends, Tomasz; Borst, Jannie
Summary: Cancer immunotherapy focuses mainly on anti‐tumour activity of CD8 + cytotoxic T lymphocytes (CTLs). CTLs can directly kill all tumour cell types, provided they carry recognizable antigens. However, CD4 + T cells also play important roles in anti‐tumour immunity. CD4 + T cells can either suppress or promote the anti‐tumour CTL response, either in secondary lymphoid organs or in the tumour. In this review, we highlight opposing mechanisms of conventional and regulatory T cells at both sites. We outline how current cancer immunotherapy strategies affect both subsets and how selective modulation of each subset is important to maximize the clinical response of cancer patients. Abstract : CD4 + T cells can either suppress or promote anti‐tumour immunity either in secondary lymphoid organs or in the tumour. This review highlights the opposing roles of conventional and regulatory T cells at both sites and outlines their effect on current cancer immunotherapy strategies.